Bawal ang plastic sa Davao a communication plan for the Plastic Bag Ban Act in Davao City act in Davao City - Mole, Sharmaine Fe L.
Plastic Bag Ban Act is an ordinance of the City Government of Davao which was recently implemented last June 28, 2012. This was carried out to address the environmental problems of the city through prohibiting the use of plastics and polystyrene foams as a food container. The city, as well, aims to entitle itself with the statement, ? Bawal ang Plastic sa Davao?. With the implementation of the aforesaid ordinance, the general public are ought to adhere to it ? requiring them to change their usual behaviors and are encouraged to use environmentally sound alternatives. To achieve the desired change that the city aims, the researchers believes that a communication plan must be created. This will serve as a communication platform on how to handle the goals and how to communicate such to the effected target audience. Prior to the creation of the plan, the researcher conducted a survey to the 300 randomly selected middle adult respondents in Brgy. Mintal, Davao City. Based from which, the researcher learned the needs, problems and weakness of the implementation of the act in the barangay and identified how further create a plan fit for their needs. The communication plan for the Plastic Bag Ban Act in Davao City aims to achieve four objectives ? raise awareness, generate interest and understanding, create appreciation, and engaging the target audience. Under these objectives are programs and activities and strategies employed to achieve the goals. More importantly, the Adult Learning Cycle was also incorporated in the study